In der Mitte Berlins 200 Jahre Kunstgeschichte an der Humboldt-Universität - Bredekamp, Horst; Labuda, Adam (humboldt-schriften zur kunst- und bildgeschichte, 2010)
In 2010, the discipline of art history at Humboldt-Universität zu Berlin celebrated its 200th anniversary. This publication offers the first summary history of the discipline in Berlin from 1810 to the present. At the beginning there was Aloys Hirt, who taught the subject of art history - together with archaeology - from antiquity to contemporary times. Academic teachers such as Herman Grimm, who became the first full professor in 1873, as well as Heinrich Wölfflin, Adolph Goldschmidt, Wilhelm Pinder and Richard Hamann shaped the subject far beyond Berlin. In addition to these outstanding protagonists, the outsiders of the subject such as Heinrich Gustav Hotho and Rudolf Arnheim are also presented. In addition to the National Socialist period, the tense post-war period at the Humboldt University is discussed, in particular the connection between university art history and the institution of the museum, which is characteristic of Berlin, as well as the visual media of art history, which are significant for the subject. In addition, the results of research on art history studies at the Friedrich-Wilhelms-Universität around 1900are presented. They allow a first approach to the hitherto least recognized area of subject and university history.